All Under Heaven; Analisis Diplomasi COVID-19 Tiongkok di Fase Awal Krisis Pandemi - Wahyu Setiyo Aji (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
ABSTRACT The Covid-19 pandemic is a shared threat that results in a multidimensional crisis. However, the response of countries was contrary to what was expected. During a pandemic crisis — at a time when international solidarity is urgently needed — countries are on the contrary “inward-looking”. The only country that emerged in the early phase of the pandemic crisis and offered assistance in handling the global pandemic was China. This raises questions about China's motives and reasons for providing foreign aid. Why did China emerge as a donor when other countries did the opposite?Culture significantly influences the direction of China's foreign policy. This can be seen in his political behavior and foreign policies issued. The provision of foreign aid in handling the Chinese pandemic is also based on traditional Chinese values, that's why this study uses Zhao Tingyang's Tianxia theory which tries to build China's view of international relations based on traditional Chinese values.How China views the world is conceptualized in the Tianxia theory. China's foreign aid for pandemic recovery believes in the concepts of internalization of world order, relational relativity, and Confucianism Improvement. These values belong only to China, which explains why China has emerged as a differentiator on the international stage.This study shows that unconventional IR theory is not just an alternative but an appropriate analytical tool to analyze specific issues. Future research is expected to find gaps in international relations and contribute to a new understanding of issues in international politics.